1
$\begingroup$

I would like to solve the differential equation $$y-y'' = \exp(-|t|),\ \ \ t \in \mathbb{R}$$ by using the Fourier transform. I have calculated the Fourier transform $\mathcal{F}(\exp(-|t|))(\xi) = \frac{2}{\sqrt{2\pi}(1+\xi^2)}$ already and went on to using the fourier transform on both sides of the equation above. Using the linearity of the Fourier operator and differentiation rules, I end up with the equation $$\int_\mathbb{R} e^{-i \xi x} y(x) \ d\lambda(x)= \frac{2}{(1+\xi^2)^2}$$ This is where I am kind of stuck... It seems like there must be a rather simple way of solving this equation for $y$, but I am not quite sure what the most straight forward way to continue would be here.. I might be able to use the inversion theorem and then solve the equation, but the calculations seem a little bit tedious.. Any help would be greatly appreciated!

$\endgroup$
1
  • $\begingroup$ You should apply the inverse transform. The convolution theorem may help. $\endgroup$ – eranreches Nov 23 '17 at 16:57
2
$\begingroup$

I have tried something, there might be something useful in it:

$$y-y''=\exp(-|t|)$$ $$\mathcal{F}(y-y'')=\mathcal{F}(\exp(-|t|))$$ $$\mathcal{F}(y)-\mathcal{F}(y'')=\frac{2}{1+\omega^2}$$ $$F(\omega)-(i\omega)^2F(\omega)=\frac{2}{1+\omega^2}$$ $$(1+\omega^2)F(\omega)=\frac{2}{1+\omega^2}$$ $$F(\omega)=\frac{2}{(1+\omega^2)^2}$$ We know that:

$\mathcal{F}(y')=i\omega\mathcal{F}(y)$

$\mathcal{F}(t\cdot y)=i \frac{\mathrm{d}}{\mathrm{d}\omega} \mathcal{F}(y)$

$\mathcal{F}(\exp(-|t|))=\frac{2}{1+\omega^2}$

$$\mathcal{F}(t\exp(-|t|))=i\frac{\mathrm{d}}{\mathrm{d}\omega}\frac{2}{1+\omega^2}=-i\frac{4\omega}{(1+\omega^2)^2}=-2 i \omega \frac{1}{(1+\omega^2)^2}=-2 i \omega F(\omega)$$ $$\mathcal{F}(y')=(i \omega) F(\omega)$$ So: $$-2\mathcal{F}(y')=\mathcal{F}(t\exp(-|t|))$$ $$-2y'=t\exp(-|t|)$$ $$y=-\frac{1}{2}\int t\exp(-|t|) \mathrm{d}t$$ If t>0: $$y=\frac{1}{2} e^{-t}(1+t)+C$$ $$y''=\frac{1}{2}e^{-t}(t-1)$$ $$y-y''=C+e^{-t}=e^{-t}$$ So $C=0$ here.

If t<0: $$y=\frac{1}{2}e^t(1-t)+C$$ $$y''=-\frac{1}{2}e^{t}(t+1)$$ $$y-y''=C+e^t=e^t$$ So $C=0$ here.

$\endgroup$
4
  • $\begingroup$ Thanks, this is very helpful. I just realised though, that I dont understand how the step $\mathcal{F}(t\exp(-|t|)) = -2i\omega F(\omega)$ works... I suppose you use the convolution theorem $\mathcal{F}(f\cdot g) = \mathcal{F}(f) * \mathcal{F}(g)$? $\endgroup$ – Markus Peschl Nov 23 '17 at 17:31
  • $\begingroup$ @GreenLogic $\mathcal{F}(t^n*f(t))=i^n*\frac{\mathrm{d}^n F(\omega)}{\mathrm{d} \omega^n}$. I will edit it a bit more soon. But this is only the particular solution for the diff. eq., I don't know how could we get the complementary solution. $\endgroup$ – Botond Nov 23 '17 at 17:45
  • $\begingroup$ @GreenLogic I think I've corrected 1 big mistake: The missing constant. $\endgroup$ – Botond Nov 23 '17 at 18:20
  • $\begingroup$ Thanks a lot again! It all makes sense now. $\endgroup$ – Markus Peschl Nov 23 '17 at 19:14

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.